2015
DOI: 10.1038/srep12675
|View full text |Cite
|
Sign up to set email alerts
|

The Dissociation of Gefitinib Trough Concentration and Clinical Outcome in NSCLC Patients with EGFR Sensitive Mutations

Abstract: Gefitinib is an essential drug for NSCLC patients harboring EGFR sensitive mutations. The approved dose 250mg/day is based on limited clinical trials, this research aims to explore the relationship between drug exposure and gefitinib response. Ctrough of 87 NSCLC patients harboring EGFR sensitive mutations were determined by LC-MS/MS. The median of Ctrough was 173.9 ng/ml (P25–P75, 130.5–231.2 ng/ml), and cutoff value 200 ng/ml was determined by X-Tile. The PFS between Ctrough < 200 ng/ml and Ctrough ≥ 200 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Haura's study indicated that gefitinib level in tumor was approximately 40-fold higher than its plasma level (29). These findings indicated that the blood C trough of gefitinib is not a good substitute indicator for its concentration in tumor, insistent with the previous research (20). Third, the ratio of gefitinib concentration in tumor to that in plasma is ranged from 1.12-250 to 1 (median 40 to 1), which demonstrated tremendous inter-individual variability (30).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Haura's study indicated that gefitinib level in tumor was approximately 40-fold higher than its plasma level (29). These findings indicated that the blood C trough of gefitinib is not a good substitute indicator for its concentration in tumor, insistent with the previous research (20). Third, the ratio of gefitinib concentration in tumor to that in plasma is ranged from 1.12-250 to 1 (median 40 to 1), which demonstrated tremendous inter-individual variability (30).…”
Section: Discussionsupporting
confidence: 74%
“…Both plasma and white blood cells were stored at −80 ℃ until analysis. The plasma of second blood was collected to measure the trough concentration of gefitinib at steady state using validated high-performance liquid chromatography with tandem mass spectrometry (LC-MS/MS) (20). EGFR mutations in primary tumors, metastatic lymph nodes or pleural effusion were detected using direct sequencing or real-time PCR (RT-PCR).…”
Section: Samples Collection and Detectionmentioning
confidence: 99%
“…Regarding to gefitinib dosage, Iressa Dose Evaluation in Advanced Lung Cancer (IDEAL-1 and –2) and NEJ002, the 500 mg dose was correlated with higher commonly rash, but the PFS and overall survival (OS) were similar [31] , [32] , [33] . What's more, steady state trough concentration of gefitinib was disassociated with PFS of patients in NSCLC patients with EGFR sensitive mutation [ 34 , 35 ], which was similar in this study ( Fig. 4 C).…”
Section: Discussionsupporting
confidence: 82%
“…An exposureresponse relationship might be expected, since the equilibrium of the bound and unbound drug will play a major role in the target occupancy. However, as shown in Table 1, in the current dosing regimens of both drugs, no relationship between plasma exposure and response has been found [21][22][23][24]. Interestingly, lower doses of erlotinib and gefitinib (25-100 mg once daily [QD] and 250 mg on alternating days, respectively) were noninferior to the approved dose of erlotinib 150 mg QD and gefitinib 250 mg QD [24][25][26][27][28][29].…”
Section: First-generation Egfr Smismentioning
confidence: 99%